2017
DOI: 10.1007/s00394-017-1540-x
|View full text |Cite
|
Sign up to set email alerts
|

Dutch food bank recipients have poorer dietary intakes than the general and low-socioeconomic status Dutch adult population

Abstract: PurposeFood-assistance program users are a specific group of nutritional concern, as they are often food insufficient and have poorer diet quality compared to non-food-assistance program users. The aim of our study was to assess dietary intake of Dutch food bank recipients (n = 167) and to compare this with dietary intake of a representative sample of the general population (Dutch National Food Consumption Survey (DNFCS-all): n = 1933), including a low-socioeconomic status (SES) sample (DNFCS-low SES: n = 312)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Suggested changes at the governmental level included improving existing resources, for example improving the quality and healthfulness of the Food Bank parcel content. Opposite to the perceptions of our participants, most participants of another Dutch study were satisfied with the food parcels and perceived them as healthy [49], even though their content did not conform to Dutch nutritional guidelines [13]. Another proposed governmental intervention was decreasing healthy food prices.…”
Section: Discussionmentioning
confidence: 89%
“…Suggested changes at the governmental level included improving existing resources, for example improving the quality and healthfulness of the Food Bank parcel content. Opposite to the perceptions of our participants, most participants of another Dutch study were satisfied with the food parcels and perceived them as healthy [49], even though their content did not conform to Dutch nutritional guidelines [13]. Another proposed governmental intervention was decreasing healthy food prices.…”
Section: Discussionmentioning
confidence: 89%
“…This could be accomplished by ensuring that food aid programs are providing healthy food baskets for low-income individuals and empowering these vulnerable individuals for healthy eating. Several countries, especially European countries, fail in their food aid programs due to a low capacity to provide nutritionally adequate foods ( 40 ). Toward this end, Portugal has recently developed and implemented a new food aid program for low-income households, which considers the nutritional and food recommendations for healthy eating ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Development of the intervention was based on the results of our previous studies in which we showed that (1) the provided amounts of saturated fat in a single-person food parcel for one single day were higher, whereas the provided amounts of fruits were lower than the nutritional guidelines [13], and (2) that the majority of the Dutch food bank recipients had lower intakes than dietary reference intakes for dietary fiber, fruit, vegetables, and fish, and a higher intake for saturated fat [16]. Based on these results, we expected to be able to improve dietary intake by providing extra fruit and vegetables to the food parcel, and remove unhealthy snacks from the food parcel.…”
Section: Development Interventionmentioning
confidence: 98%